Effect of microstructure of quantum dot layer on electroluminescent properties of quantum dot light emitting devices - Yoon, S.-L.; Jeon, M.; Lee, J.-K. (2013)
Quantum dots(QDs) with their tunable luminescence properties are uniquely suited for use as lumophores in light emitting device. We investigate the microstructural effect on the electroluminescence(EL). Here we report the use of inorganic semiconductors as robust charge transport layers, and demonstrate devices with light emission. We chose mechanically smooth and compositionally amorphous films to prevent electrical shorts. We grew semiconducting oxide films with low free-carrier concentrations to minimize quenching of the QD EL. The hole transport layer(HTL) and electron transport layer(ETL) were chosen to have carrier concentrations and energy-band offsets similar to the QDs so that electron and hole injection into the QD layer was balanced. For the ETL and the HTL, we selected a 40-nm-thick ZnSnOx with a resistivity of 10Ω·cm, which show bright and uniform emission at a 10V applied bias. Light emitting uniformity was improved by reducing the rpm of QD spin coating.At a QD concentration of 15.0mg/mL, we observed bright and uniform electroluminescence at a 12V applied bias. The significant decrease in QD luminescence can be attributed to the non-uniform QD layers. This suggests that we should control the interface between QD layers and charge transport layers to improve the electroluminescence. ？ Materials Research Society of Korea.
Keywords: Electroluminescent properties; Electron transport layers; Free carrier concentration; Inorganic semiconductors; Light emitting devices; Micro-structural effects; Quantum dot leds; Semiconducting oxide films; Amorphous films; Carrier concentration; Coatings; Electroluminescence; Light; Luminescence; Oxide films; Semiconductor quantum dots